Intervención de enfermería en pacientes con traumatismo craneoencefálico: revisión sistemática - Santiago Ramírez, Olga Magali (2025)
Introduction: TBI is a disease acquired daily in different health institutions, a situation that has led to the nursing team having to adopt efficient and timely mechanisms for people who suffer from it to significantly improve their conditions, depending on the sequelae left by the pathology, which is why it is very important that the nursing staff responsible for the care of these patients in order that they may have the necessary knowledge to obtain a good assessment. It is also important for health institutions to establish updated guidelines in a protocol for the care of these patients according to the clinical picture that they present and to provide continuous training to the nursing unit so that it can be applied in a convergent, fast and practical manner. Methodology: The research was carried out using a qualitative approach with a systematic design, which followed a theoretical study, in which analytical - synthetic, inductive - deductive, historical - logical and empirical methods of knowledge were used. Results: The present research makes clear the importance of the active role of nursing in critical care units, since it is essential to detect in a timely manner the slightest variations in the condition of the patient. Conclusions: The systematic review showed that complications depend on the degree of affectation produced in the patient, and that the work carried out by the nursing staff is paramount in terms of the care provided.